20 ways to make every day better : simple, practical changes with real results - Meyer, Joyce, 1943- (Faith Words, 2017)
"#1 New York Times bestselling author Joyce Meyer shares powerful, practical ways to experience a new level of joy and excitement about life every day,"--Amazon.com.